The invasive Lespedeza cuneata attracts more insect pollinators than native congeners in tallgrass prairie with variable impacts - Woods, Teresa Marie; Jonas, Jayne L.; Ferguson, Carolyn J. (My University, 2012)
Invasive plant species can potentially exert competitive or facilitative effects on insect pollination services of native species. Factors that influence these effects include the degree of shared pollinator species, synchronous flowering phenology, similar flower morphology and color, relatedness of invasive and natives, and showiness and densities of flowers. We investigated such plant-pollinator dynamics by comparing the invasive Lespedeza cuneata and three native congeners, all sympatric with synchronous flowering, using in situ populations over two years during peak floral displays. Insect visitation rates of the invasive were significantly higher per plant in both years than on the native species. The invasive exerted a competitive effect on visitation of two native species, and a facilitative effect on visitation of the native species with the highest degree of shared insect visitors. Positive correlations were found between floral density and visitation rate per plant in all the native species. Although no such correlation was found for the invasive, floral density in L. cuneata was at least twenty times higher than in the native species and likely saturated the pollinator community. Analyses of insect visitor taxonomic data indicated the insect communities visiting each of the Lespedeza species were generally similar though with species-specific differences. The main exception was that the common honeybee, Apis mellifera, was a primary visitor to the invasive plant species, yet was never observed on the native Lespedeza species.
Keywords: Apis mellifera; Lespedeza; Invasive; Mixed mating system; Pollination